The European Union Taxonomy – The Revolution of Sustainable Activities - Maria-Mădălina Bogeanu-Popa; Mariana Man (Ovidius University Annals: Economic Sciences Series, 2022)
This paper represents qualitative research of the concept of taxonomy within the European Union (EU), drafted with the sole purpose of establishing the presence of the environmental elements specific to sustainable development within the economic activity. The EU taxonomy is an important mechanism which offers coherence in using every instrument conceived for accomplishing the ecological objectives of the environment. The concept of taxonomy refers to the investment funds of big economic entities within EU and beyond, which need to provide information about their environmental related activities. The purpose of this paper is to highlight the cooperation between the regulation authorities and the technical experts in the domain (TEG), which offer a starting point in this journey from their experience with environmental, social and governance (ESG) information reporting. Therefore, the intention EU has regarding the taxonomy is guiding the capital towards the ecological and the implementation of a new universally available classification system of sustainable investments at an international level.